1959
DOI: 10.1111/j.1469-8137.1959.tb05351.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsiventrality of Leaf Primordia

Abstract: summary When in shoot apices of potatoes the presumptive area of I1, the next leaf due to arise, or of 12, was isolated from the growing‐point by a vertical cut, the isolated pieces regularly formed dorsiventral leaves, even when slips of mica were left in the cuts. These results differ from those of Sussex, who reported that he obtained radial leaves from nearly similar operations on potatoes, and interpreted them as due to interruption of an induction of dorsiventrality by the apex. The difference in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…Given that PHB and PHV confer adaxial identity (Emery et al, 2003;McConnell and Barton, 1998), the adaxialization of jba-1D leaves seems counterintuitive. However, experiments have shown that a SAM-derived signal(s) is important for specifying adaxial leaf identity (Snow and Snow, 1959;Sussex, 1954;Waites and Hudson, 1995), and thus initiating jba-1D leaves may receive an excess of adaxializing signal(s) emanating from multiple SAMs. Increased accumulation of transcripts from REV, which plays a redundant role with PHB and PHV in conferring adaxial fate (Emery et al, 2003), may also contribute to conditioning this phenotype, as increased meristem size per se is not sufficient to cause leaf adaxialization (Clark et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Given that PHB and PHV confer adaxial identity (Emery et al, 2003;McConnell and Barton, 1998), the adaxialization of jba-1D leaves seems counterintuitive. However, experiments have shown that a SAM-derived signal(s) is important for specifying adaxial leaf identity (Snow and Snow, 1959;Sussex, 1954;Waites and Hudson, 1995), and thus initiating jba-1D leaves may receive an excess of adaxializing signal(s) emanating from multiple SAMs. Increased accumulation of transcripts from REV, which plays a redundant role with PHB and PHV in conferring adaxial fate (Emery et al, 2003), may also contribute to conditioning this phenotype, as increased meristem size per se is not sufficient to cause leaf adaxialization (Clark et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These asymmetries are established relatively early during leaf development and are defined relative to the SAM. Surgical experiments designed to examine the relationship between leaf development and the SAM demonstrated that communication between the SAM and leaf primordia is necessary for the establishment of the adaxial-abaxial pattern and for leaf outgrowth (Sussex, 1955;Snow and Snow, 1959). These experiments suggested the existence of a SAM-derived signal that is necessary for the establishment of adaxial-abaxial leaf polarity.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, signals that emanate from the meristem act to promote development of the adaxial domain of leaves. Incisions that isolate the incipient leaf primordium from the meristem result in radialized leaves that lack an adaxial domain (Sussex, 1954;Sussex, 1955;Snow and Snow, 1959). This suggests that in the absence of the signal(s) from the meristem, the default state is development of the abaxial domain.…”
Section: The Role Of Meristem Signals and Polarity Genesmentioning
confidence: 99%